Transient expression of the diseased phenotype of osteoarthritic chondrocytes in engineered cartilage. Issue 4 (29th May 2016) - Silverstein, Amy M.; Stoker, Aaron M.; Ateshian, Gerard A.; Bulinski, J. Chloe; Cook, James L.; Hung, Clark T.
ABSTRACT: Due to the degradation of osteoarthritic (OA) cartilage in post‐traumatic OA (PTOA), these tissues are challenging to study and manipulate in vitro. In this study, chondrocytes isolated from either PTOA (meniscal‐release (MR) model) or normal (contralateral limb) cartilage of canine knee joints were used to form micropellets to assess the maintenance of the OA chondrocyte phenotype in vitro. Media samples from the micropellet cultures were used to measure matrix metalloproteinase (MMP), chemokine, and cytokine concentrations. Significant differences in matrix synthesis were observed as a function of disease with OA chondrocytes generally synthesizing more extracellular matrix with increasing time in culture. No donor dependent differences were detected. Luminex multiplex analysis of pellet culture media showed disease and time‐dependent differences in interleukin (IL)‐8, keratinocyte chemoattractant (KC)‐like protein, MMP‐1, MMP‐2, and MMP‐3, which are differentially expressed in OA. This memory of their diseased phenotype persists for the first 2 weeks of culture. These results demonstrate the potential to use chondrocytes from an animal model of OA to study phenotype alterations during the progression and treatment of OA. © 2016 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 35:829–836, 2017.